SYNTHESIS OF BUTHYL BROMIDE LABELED 82Br FOR LEAKAGE DETECTION APPLICATION IN INDUSTRIAL PIPELINE SYSTEM - Ade Suherman; Titin Sri Mulyati; Iswahyudi Iswahyudi; Badra Sanditya Rattyananda; Dessy Cartika; Winda Putri Silpia; Mentik Hulupi; Duyeh Setiawan; Muhamad Basit Febrian (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2019)
The detection of a leakage in an installation or pipeline in industrial complex is difficult to be done because related to security, safety, and operation condition. With expanded radioisotope application as a tracer in industry, hence a leakage in a pipe can be detected easily and qiuickly without needed excavation or stop the production process. The selection of radioisotope labeled compound as radiotracer should be examined carefully to determine the appropriate and well mixed radiotracer with the material passing through the pipeline system. Radioisotope labeled compound butyl bromide-82 (C4H982Br) as a radiotracer can be synthesized by reacting K82Br with 1-butanol and sulphuric acid (H2SO4) as a catalyst. The experiment result shows that synthesized C4H982Br by composition of 15 mL K82Br solution (0.1 gr/mL KBr) and 10 mL 1-butanol gave the highest percentage of reactions amount 50,00% and 40,95%. Characterization by FTIR showed that the product has absorption band for C-Br at 514,99-738,74 cm-1. GCMS analysis showed the peak of C4H982Br together with other 7 peaks of impurities with 43.03% percentage of C4H982Br peak. In distribution coefficient determination of C4H982Br in the test solution from industry (ethylene dichloride), Kd value of 5,1350 was obtained and more than 98% C4H982Br distilled together with ethylene dichloride in 110°C distillation process whereas no radioactivity detected in distillation flask if K82Br was used. Based on these results, C4H982Br is suitable to be applied as radiotracer for leakage detection in pipeline system with organic compounds as passing liquid including ethylene dichloride.